Facile and Scalable Synthesis of Copolymer-Sulfur Composites as Cathodes for High Performance Lithium-Sulfur Batteries. (21st June 2017) - Liu, Jingjing; Campbell, Brennan; Ye, Rachel; Bell, Jeffrey; Mutlu, Zafer; Li, Changling; Yan, Yiran; Ozkan, Mihri; Ozkan, Cengiz
ABSTRACT: To promote the energy density of lithium-ion battery, the sulfur-based cathode has attracted extensive attention because of its high specific capacity of 1672 mAh g -1 and its high abundance. However, the sulfur shuttling effects and the loss of active material during lithiation hinder its commercial application. To tackle these issues, we synthesized a stable copolymer-sulfur composite by chemically binding sulfur. The composite with 86% sulfur content was prepared using 1, 3-diethynylbenzen and sulfur particles via scalable invers vulcanization. The sulfur content in copolymer sulfur was achieved as high as 86%. Our copolymer-sulfur composite cathode showed excellent cycling performance with a specific capacity of 454 mAh g -1 at 0.1 C after 300 cycles. We demonstrate that the organosulfur-DEB units in the copolymer-sulfur composite serve as the 'plasticizer' to effectively prevent the polysulfide shuttling.